Application of cisplatin and other platinum-containing drugs in cancer therapy: Comprehensive review - A.S Arul Prishya; Chopra Lalita; Manikanika; Bose Diotima; Chauhan Ashish Singh; Alhadrawi Merwa; Chauhan Abhineet; Kumar Dharminder (E3S Web of Conferences)
A well-known chemotherapy medication is a cisplatin, also referred to as cis-diamminedichloroplatinum or cisplatinum(II). Cancers such as bone metastases, lymphomas, germ cell tumors, and carcinomas can all be treated with it. Its mode has been takenpertaining to its capability to cross-link with purine biological branches, obstructing DNA repair processes, generating DNA damage, and, as a result, cancerous cells undergo apoptosis. Nevertheless, due to drug resistance and a number of unfavorable side effects, including severe kidney problems, allergic reactions, lowered immunity to infections, gastrointestinal problems and others, have also been used. For overcoming drug resistance and reducing adverse effects, cisplatin- based combination therapies with other pharmaceuticals have also garnered considerable investigation. This in-depth analysis looks at the isotopes of the properties cisplatin and associated platinum-based drugs, as well as how they can be is employed to treat a range of health maligancies. Particular focus is placed on its unfavorable side effects and molecular mechanisms of action. The current paper provides a pharmacological assessment of the drug, outlining its clinical applications, toxic effects, and mechanisms of resistance. The ability of cisplatin to form DNA adducts by crosslinking with urine bases on DNA has been connected to its mode of action. As a result, cancer cells experience apoptosis, which stops DNA damage from being repaired. The drug does, however, display certainly improved DNA damage repair, decreased drug accusation inside cells, and cisplatin deactivation in the cytosol are all signs of resistance. The drug also has some negative adverse consequences, including vomiting, kidney damage, cardiotoxicity, liver toxicity, and neurodegeneration.